Short Sleep Duration and Skipping Main Meals among University Students - Jéssika Patatas de-Arruda; Ana Paula Alves de-Souza; Lídia Pitaluga Pereira; Lorena Barbosa Fonseca; Patrícia Simone Nogueira; Paulo Rogério Melo Rodrigues; Ana Paula Muraro; Márcia Gonçalves Ferreira (Sleep Science)
Introduction Admission to university influences lifestyle behaviors and is marked by a daily routine of accumulation of activities that can interfere with sleep duration, affecting food choices and meal consumption habits throughout the day.